Pengaruh Aromaterapi Digital Diffuser terhadap Tingkat Kecemasan Ibu Bersalin Kala I - Veronika Yunitasari; Agustini Liviana Dwi Rahmawati; Devin Mahendika; Cakrawati R; Rezqiqah Aulia Rahmat (Barongko: Jurnal Ilmu Kesehatan, 2026)
Background: Maternal anxiety during the first stage of labor can affect the course of labor, the duration of contractions, and fetal well-being. Non-pharmacological interventions such as aromatherapy are an option to reduce anxiety. The use of a digital diffuser as a medium for aromatherapy distribution provides a more even and consistent distribution of aroma. Objective: To determine the effect of digital diffuser aromatherapy on maternal anxiety levels during the first stage of labor. Methods: This was a quasi-experimental study with a pretest-posttest design with a control group. Forty mothers in the first stage of labor were divided into an intervention group (n=20) and a control group (n=20). The intervention group was given lavender aromatherapy via a digital diffuser for 15 minutes, while the control group received standard care. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS). Data were analyzed using the Wilcoxon and Mann-Whitney tests. Results: The average anxiety score before the intervention in the intervention group was 25.4 (moderate category) and decreased to 14.2 (mild category) after the intervention (p < 0.05). The control group did not experience a significant decrease (from 24.8 to 23.9). The Mann-Whitney test showed a significant difference between the two groups (p < 0.05). Conclusion: Digital diffuser aromatherapy effectively reduces maternal anxiety levels during the first stage of labor. Healthcare providers are advised to use this method as a non-pharmacological complementary therapy in managing labor anxiety.